A Comparative Study of the Artificial Evaporation of Underground and Sea Brines - Vaithyanathan, C.; Umayoru Bhagan, V. (Asian Journal of Chemistry, 2010)
Evaporation of underground and sea brines were monitored artificially. The rates of evaporation for both the samples were almost same. Various parameters were analyzed at different Baume degrees. A comparative study was carried out regarding the presence of Ca2+, K+, Mg2+, Cl-, SO42- ions and sodium chloride in both samples.